VARICOCELE AS A FACTOR IN IMPAIRED SPERMATOGENESIS AND REDUCED MALE FERTILITY - Turdiyev Doston Shavkatovich; Raupov Abdurahmon Ortiq o’g’li (KONFERENSIYALAR, 2025)
Аnnotation. For years, varicocele treatment has been a key focus in urology-andrology due to its high prevalence and significant role in male subfertility and infertility. Despite extensive research, the etiology, pathogenesis, and treatment remain debated. A review of 60 sources (11 domestic, 49 foreign) highlights the need for effective management strategies. Treatment aims to restore reproductive function, improve fertility, and minimize recurrence and complications.